Fiber‐Shaped Energy‐Storage Devices: Recent Advances in Fiber‐Shaped Supercapacitors and Lithium‐Ion Batteries (Adv. Mater. 5/2020). Issue 5 (4th February 2020) - Zhou, Yang; Wang, Chun‐Hui; Lu, Wen; Dai, Liming
Abstract : In article number 1902779, Chun‐Hui Wang, Wen Lu, Liming Dai, and Yang Zhou present a comprehensive review on recent advances in fiber‐shaped supercapacitors and lithium‐ion batteries, along with next‐generation wearable electronics with high performance and comfort.